PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP LOYALITAS KONSUMEN PADA SITUBONDO SPORT CENTER FUTSAL KABUPATEN SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Noer, Anugrah Ramadhani; Kusnadi, Edy; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2022)
Marketing management can be defined as the analysis, planning, implementation and control of programs designed to create, build and maintain profitable exchanges with target markets with a view to achieving organizational goals.The purpose of this study was to analyze and examine the effect of service quality and facilities on consumer loyalty through consumer satisfaction. The population in this study are consumers from the Situbondo Sport Center Futsal, Situbondo Regency. The sampling technique was determined by the simple random sampling method. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that service quality has a significant positive effect on consumer satisfaction, facilities have a significant positive effect on consumer satisfaction, service quality has a significant positive effect on consumer loyalty, facilities have a negative but not significant effect on consumer loyalty, satisfaction consumers have a significant positive effect on consumer loyalty, service quality on consumer loyalty through customer satisfaction has a negative but not significant effect, facilities on consumer loyalty through customer satisfaction have a significant positive effect.